Analisis Interpretasi Tugu Parameswara di Bundaran Jakabaring - Palembang - Patriansyah, Mukhsin (Jurnal Seni, Desain dan Budaya)
ABSTRACTThis Parameswara monument is a sculpture artwork created to welcome PON 2004 ago. Analysis of this work will use the aesthetic approach, in addition to its monumental form of this work is also closely related to the history of Palembang as the center of the greatest kingdom civilization in the archipelago of the archipelago of Sriwijaya. As one of the great kingdom of Sriwijaya kingdom has a strong influence on the earth archipelago. This is evident until now from the traces he left behind. Likewise with the work of sculpture Parameswara is a work of sculpture symbolic abstraction created by Rita Widagdo. Rita Widagdo is one of the artists living in modren age, this is certainly very influential in the creation of this sculpture artwork. The presence of sculpture art works also provide an interpretation of the development of the times. Parameswara sculpture is not just a beautiful natural manifestation of natural simplification by simply capturing the essence of an object in the amatinya, the object is a creative stimulus so that the resulting work is an abstraction of reality. In the manifestation Rita Widagdo tends to use a concave and convex lines firmly to give the impression of a courage and strength that is the result of interpretation of Parameswara figures. Parameswara statue is a symbol of unifying Malay clumps in the archipelago. The reason, almost all Malays in the archipelago, especially in Malaysia, Singapore, southern Thailand, and Brunei originated from Palembang. They are all descendants of Parameswara and his followers, a commander of Palembang After the fall of Sriwijaya, Iskandar Shah or Parameswara fled north to find a new settlement.Keywords: Sriwijaya, Parameswara, Interpretation, Symbolic AbstractionABSTRAKTugu Parameswara ini merupakan karya seni patung yang dibuat untuk menyambut? PON 2004 yang lalu. Analisis karya ini? nantinya menggunakan pendekatan estetika, di samping bentuknya yang monumental karya ini juga erat kaitannya dengan sejarah kota Palembang sebagai pusat peradaban kerajaan terbesar di bumi Nusantara yakni kerajaan Sriwijaya. Sebagai salah satu kerajaan besar tentu kerajaan Sriwijaya memiliki pengaruh yang kuat di bumi Nusantara. Hal ini terbukti sampai saat sekarang dari jejak-jejak yang ditinggalkannya. Begitu juga dengan karya seni patung Parameswara merupakan karya seni patung abstraksi simbolik yang diciptakan oleh Rita Widagdo. Rita Widagdo merupakansalah satu seniman yang hidup dizaman modren, hal ini tentu sangat berpengaruh dalam penciptaan karya seni patung ini. Kehadiran karya seni patung ini turut memberikan interpretasi atas perkembangan zaman. Karya patung Parameswara bukan sekedar manifestasi alam yang indah melaikan simplifikasi alam dengan hanya menangkap hakikat dari sebuah objek yang di amatinya, objek tersebut merupakan rangsang cipta sehingga karya yang dihasilkan merupakan abstraksi dari realitas. Dalam perwujudannya Rita Widagdo cendrung menggunakan garis cekung dan cembung dengan tegas sehingga memberikan kesan suatu keberanian dan kekuatan yang merupakan hasil dari interpretasi terhadap tokoh Parameswara. Patung Parameswara merupakan simbol pemersatu rumpun Melayu di Nusantara. Pasalnya, hampir? semua orang Melayu yang ada di Nusantara, khususnya di Malaysia, Singapura, Thailand Selatan, dan Brunei berasal dari Palembang. Mereka semua keturunan dari Parameswara dan pengikutnya, seorang panglima dari Palembang Setelah jatuhnya Sriwijaya, Iskandar Shah atau Parameswara melarikan diri ke utara untuk menemukan sebuah pemukiman baru.Kata kunci : Sriwijaya, Parameswara, Interpretasi, Abstraksi Simbolik